The pandemic and the challenges of development in a Colombian region: The case of the Metropolitan Area of Bucaramanga - Gamboa Vesga, Yudy Adriana; Delgado Jaimes, Pedro Fernando; Ortiz Isarra, Dairo Rubiel; León Castañeda, Yany Lizeth (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
COVID-19 generated a health, economic and social crisis of great proportions in almost every country in the world. Colombia suffered in 2020 the worst economic contraction in its recent history and the achievements made in recent years in the fight against poverty have been reversed. Bucaramanga and the cities that make up its metropolitan area (AMB), have not been immune to this situation. In this context, this research investigates in depth the effects of the COVID-19 pandemic in AMB and the challenges that arise from these for local development. In 2015 Bucaramanga was selected by the World Bank as one of the most competitive cities in the world.